Beyond Borders: On the Transgressive Potential of Romani Literature(s) - Granqvist, Kimmo; von Hagen, Kirsten; Ortrud Hertrampf, Marina; Kledzik, Emilia; Toninato, Paola (Porównania, 2025)
The article "Beyond Borders: On the Transgressive Potential of Romani Literature(s)" explores the evolving field of Romani literatures within a broader sociopolitical and aesthetic context, focusing particularly on its transgressive, boundary-crossing potential. Written by scholars Kirsten and Emilia, who approach the topic from a migration studies perspective, the article emphasizes the complexity, diversity, and underrepresentation of Romani literary production in both academic discourse and mainstream cultural canons. Romani and Sinti communities, estimated at around eight million across Europe, do not represent a homogeneous group but a diasporic mosaic marked by linguistic, cultural, and geographic diversity. This heterogeneity is mirrored in their literary expressions. Though Romani written literature is a relatively recent phenomenon—emerging in the past century—it is a growing and increasingly significant field. The establishment of the International Romani Writers' Association (IRWA) in 2002 stands as testament to this development. Scholars debate whether “Romani literature” should be referred to in the plural to reflect its internal diversity. Despite historic resistance within some Romani communities to literary production—especially in majority languages such as French—an increasing number of Romani authors have embraced literature as a means of cultural expression and political engagement. Writers such as Mateo Maximoff, Sandra Jayat, and Miguel Haler are notable for consciously navigating the space between Romani identity and majority societies, often acting as cultural mediators. The article situates Romani literature within the broader framework of migration literature. While Roma mobilities have long been studied from sociological and anthropological perspectives—especially post-WWII and after the fall of the Iron Curtain—their literary implications remain underexplored. The article challenges traditional diaspora concepts, noting critiques from scholars like Paola Toninato and Ileana Chirila, who highlight the problematic framing of Roma as “eternal nomads.” Such narratives often serve to further marginalize Roma rather than to understand their lived experiences.